LEVERAGING ARTIFICIAL INTELLIGENCE (AI) FOR EDUCATIONAL DEVELOPMENT IN NIGERIA: EXAMINING THE CHALLENGES AND OPPORTUNITIES - Daddie, Joel Augustus; Victor Iheanyichukwu, Asiegbu; Esther, Obinna (Journal of Social Science, 2025)
Objective: This study aims to explore the challenges and implications of using Artificial Intelligence (AI) as a pedagogical tool to enhance education in Nigeria. Specifically, it examines the potential obstacles and opportunities AI presents for educational growth and development in the Nigerian context. Method: The research adopts an exploratory approach, utilizing secondary data sources such as textbooks, published papers, internet resources, and newspaper reports. The data were organized thematically and analyzed through content analysis, guided by the connectivism learning theory as the analytical framework. Results: The findings indicate that AI has the potential to customize learning experiences to suit individual student needs, abilities, and learning styles. It can provide personalized support through real-time feedback, enhancing the overall learning process. Novelty: This study contributes to the discourse on integrating AI in education by highlighting its potential to improve Nigeria's educational system. It emphasizes the need for government investment in AI-driven educational tools, the enhancement of teaching materials, and curriculum development to foster a more scientific and globally competitive educational environment.